CONFIGURATION SYSTEM AND TRANSMISSION CONTROL PROTOCOL / INTERNET PROTOCOL (TCP / IP) ON WINDOWS SERVER 2003 - Sunarso Sunarso; Indrianto, SKom, MT Indrianto, SKom, MT (Jurnal Sistem Komputer, 2004)
One very important thing to note in order to enter and take advantage of theglobalization of this information, it is a fairly reliable technical knowledge in datacommunication.To be able to utilize the resources of existing data required a computer system thatcan connect the user (the user) with the source data. That is, with the use of theImplementation and Configuration Transmission Control Protocol / Internet Protocol(TCP / IP) in Windows Server 2003 which is one of the operating system protocol.